Survival and Revival in Sweden's Court and Monarchy, 1718–1930 - Persson, Fabian. author. aut Link
XXVI, 349 p. 20 illus.
Keywords: This book will be the first to deeply analyze the Swedish court and monarchy through a longue duree perspective to show the crucial role of the court in maintaining a relationship between the monarchy and nobility throughout the eighteenth and nineteenth centuries. Sweden offered a different type of monarchy in comparison to the more often studied French and British monarchies. Sweden's court system successfully managed several coups and upheavals and maintained strong royal power throughout many transitions. Studying the Swedish model offers insights into how courts functioned in European principalities in general by providing a resilient and flexible framework for royal authority in tandem with the nobility. Based on extensive research conducted in the Swedish National Archives, the Palace Archives, and the Royal Library, the book presents some never-before published case studies and materials that drive the impact of court studies on many different areas of research, including gender studies, political science, and art history. .